Sensory neuro-immune interactions differ between Irritable Bowel Syndrome subtypes. Issue 10 (5th July 2012) - Hughes, Patrick A; Harrington, Andrea M; Castro, Joel; Liebregts, Tobias; Adam, Birgit; Grasby, Dallas J; Isaacs, Nicole J; Maldeniya, Lochana; Martin, Chris M; Persson, Jenny; Andrews, Jane M; Holtmann, Gerald; et al.
Abstract : Objective: The gut is a major site of contact between immune and sensory systems and evidence suggests that patients with irritable bowel syndrome (IBS) have immune dysfunction. Here we show how this dysfunction differs between major IBS subgroups and how immunocytes communicate with sensory nerves. Design: Peripheral blood mononuclear cell supernatants from 20 diarrhoea predominant IBS (D-IBS) patients, 15 constipation predominant IBS (C-IBS) patients and 36 healthy subjects were applied to mouse colonic sensory nerves and effects on mechanosensitivity assessed. Cytokine/chemokine concentration in the supernatants was assessed by proteomic analysis and correlated with abdominal symptoms, and expression of cytokine receptors evaluated in colonic dorsal root ganglia neurons. We then determined the effects of specific cytokines on colonic afferents. Results: D-IBS supernatants caused mechanical hypersensitivity of mouse colonic afferent endings, which was reduced by infliximab. C-IBS supernatants did not, but occasionally elevated basal discharge. Supernatants of healthy subjects inhibited afferent mechanosensitivity via an opioidergic mechanism. Several cytokines were elevated in IBS supernatants, and levels correlated with pain frequency and intensity in patients. Visceral afferents expressed receptors for four cytokines: IL-1β, IL-6, IL-10 and TNF-α. TNF-α most effectively caused mechanical hypersensitivity which was blocked by a transient receptor potential channel TRPA1 antagonist. IL-1β elevated basal firing, and this was lost after tetrodotoxin blockade of sodium channels. Conclusions: Distinct patterns of immune dysfunction and interaction with sensory pathways occur in different patient groups and through different intracellular pathways. Our results indicate IBS patient subgroups would benefit from selective targeting of the immune system.